2021
DOI: 10.12688/f1000research.28318.1
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation in populations of Mycobacterium tuberculosis endemic to the Indian Ocean Rim

Abstract: Background: Lineage 1 (L1) and 3 (L3) are two lineages of the Mycobacterium tuberculosis complex (MTBC) causing tuberculosis (TB) in humans. L1 and L3 are prevalent around the rim of the Indian Ocean, the region that accounts for most of the world’s new TB cases. Despite their relevance for this region, L1 and L3 remain understudied. Methods: We analyzed 2,938 L1 and 2,030 L3 whole genome sequences originating from 69 countries. We reconstructed the evolutionary history of these two lineages and identified gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 82 publications
0
20
1
Order By: Relevance
“…Associations between each of these sublineages with geography have been studied. For example, L1.1.1.1 is predominant in Vietnam 7 , L1.1.3 is common in Myanmar 8 , Bangladesh 9 and East Africa 10 while L1.1.2.2 and L1.2.2 (previous L1.2.1) are associated with India and Southeast Asia, respectively 5 . Interestingly, around 80% of Mtb isolates in the Philippines, a high TB burden country, belonged to the last sublineage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Associations between each of these sublineages with geography have been studied. For example, L1.1.1.1 is predominant in Vietnam 7 , L1.1.3 is common in Myanmar 8 , Bangladesh 9 and East Africa 10 while L1.1.2.2 and L1.2.2 (previous L1.2.1) are associated with India and Southeast Asia, respectively 5 . Interestingly, around 80% of Mtb isolates in the Philippines, a high TB burden country, belonged to the last sublineage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Among other studies that inferred the clock rate for L2, most confirmed a moderately high rate (∼ 1×10 −7 , Merker et al 2018, Rutaihwa et al 2019, Torres Ortiz et al 2021), while one estimated a higher rate of evolution (∼ 3×10 −7 , Eldholm et al 2016). The only additional study to attempt the estimation of the clock rate of L1 found a lack of a temporal signal (Menardo et al 2021). Altogether the available evidence is limited, and more precise estimates are needed to understand whether the rate of molecular evolution contributes to the different clustering rates and TBL for L1 and L2.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on the historical connection between two locally endemic clones could only be obtained thanks to the availability of public Short Read Archives and to the development of a new bioinformatical pipeline that analyses more than 50,000 characters that builds highly resolutive phylogenetic trees, and includes repeated sequences information (PE-PPE genes, CRISPR and Insertions sequences). With the increasing power of computational analysis of genomes and using supercomputing centers, it now becomes possible to analyze not only Single-Nucleotide Polymorphisms, but also repetitive sequences, which paradoxically were at the start of molecular epidemiology [91-93], however whose analysis was almost totally supplanted by WGS [56,57,94]. Going more in-depth into the complex historical phylodynamics history of all MTC lineages (made up of various waves of expansion and extinction history) will be facilitated by the use of all available markers and the increase into study size, towards 100,000 genomes analysis, to better disentangle all the threads between ancient and recent historical event that shaped today's pandemia, and to obtain an improved understanding of the historical pandemic in relation to ancient/modern population migrations [8,95,96].…”
Section: Discussionmentioning
confidence: 99%